2018
DOI: 10.1016/j.dld.2018.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between periampullary diverticula and biliopancreatic disease? An EUS approach to answer the question

Abstract: Whereas PADs were linked with history of cholangitis, CBD stones and dilation, no association was found with pancreatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…A recent study by Bruno et al [5] confirmed an association between diverticula and choledocholithiasis, cholangitis and common bile duct dilatation in an Endoscopic Ultrasound (EUS) study of the prevalence of DD. In addition, no significant association was found between the presence of DD and acute, recurrent or chronic pancreatitis, as in the present study.…”
Section: Primary Choledocholithiasis Was Detected Less Frequently In mentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study by Bruno et al [5] confirmed an association between diverticula and choledocholithiasis, cholangitis and common bile duct dilatation in an Endoscopic Ultrasound (EUS) study of the prevalence of DD. In addition, no significant association was found between the presence of DD and acute, recurrent or chronic pancreatitis, as in the present study.…”
Section: Primary Choledocholithiasis Was Detected Less Frequently In mentioning
confidence: 85%
“…Second, it is possible that diverticula cause the sphincter to spasm, thereby increasing biliary duct pressure that may in turn produce jaundice and cholangitis, as well as increase the chance of biliary stone formation. Finally, DD can compress the distal part of the common bile duct, causing functional biliary stasis [2,5,35].…”
Section: Discussionmentioning
confidence: 99%
“…During duodenoscopy, the presence of peripapillary diverticulum and peripapillary fistula was recorded. Peripapillary diverticulum was defined as the presence of a diverticulum within 2 cm radius from the papilla, it is known that duodenal diverticulum is associated with choledocholithiasis and cholangitis 8,9 . Peripapillary fistula is a common complication of common bile duct stones and it is related to cholangitis 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Periampullary diverticulum refers to the saclike process formed within a radius of about 3cm around the large duodenal nipple. At present, the existence of periampullary diverticulum and choledocholithiasis, cholangitis, and choledochal dilatation is considered to be significantly related [16]. Other studies have shown that patients with common bile duct stones are more likely to be found combined with periampullary diverticulum and that the periampullary diverticulum is only related to common bile duct stones but not to gallbladder stones [17].…”
Section: Introductionmentioning
confidence: 99%